Information-based interactive services and support system - Amanullah, Md; Zeki, Akram M.; Ibrahim, Adamu Abubakar (Institute of Electrical and Electronics Engineers Inc., 2018)
The fact that information-based interaction designed requires user involvement, Service Desk System (SDS) is necessary for collecting, tracking and processing requests for IT service support. The system can be dynamic, where many approaches can be used depending on the objective of the tasks at hand. Currently, Kulliyyah of Information and Communication Technology (KICT), International Islamic University Malaysia (IIUM) SDS do not cover a lot of evolving user's tasks. As a result, the main aim of this study is to propose interactive SDS for students and staffs at KICT, IIUM. The architectural framework of the system has been formulated to include all the necessary requirements that might have arisen over time. There are some drawbacks in the process of the current system which affects the whole management process of the organization. With the aid of the framework, a prototype has been implemented. This prototype is established using the Hypertext Markup Language (HTML), PHP with the support of Cascading Style Sheets (CSS3), Bootstrap and JavaScript along with MySQL as the database. The developed system is an online (web-based) system which allows users to request information in order for the administrator to respond promptly, which shows the efficiency and reliability of the system